Purification of Human Immunoglobulin G with Bathophenanthroline–Zn2+, –Fe2+, or –Cu2+ Complexes - Thisara Jayawickrama Withanage; Ron Alcalay; Olga Krichevsky; Ellen Wachtel; Ohad Mazor; Guy Patchornik (Antibodies)
Background/Objectives: Pharmaceutical companies are aware of the ongoing effort to satisfy the increasing global demand for therapeutic-grade monoclonal antibodies (mAbs), an especially difficult challenge for poor and developing countries. We present a simple, economical, single-step purification approach at neutral pH for polyclonal human IgG (hIgG), which does not require any expensive ligands, chromatography columns, polymers, or membranes. Methods/Results: Instead, porous precipitates of commercial, recyclable aromatic [bathophenanthroline:cation] complexes were found to efficiently capture impurity proteins from CHO cells or E. coli lysate while maintaining the majority of the highly concentrated hIgG (5–15 mg/mL) in the supernatant. [(Batho)3:Zn2+] complexes were the most promising, resulting in hIgG with a purity of ≈95%, by SDS-PAGE. This purified hIgG is monomeric (by dynamic light scattering, DLS) and preserves the native secondary structure (by far UV circular dichroism spectroscopy, CD). The process yield is >90% (by densitometry) and is maintained after a 100-fold increase in the reaction volume, which required only proportional increases in reagents. Conclusions: Although Protein A chromatographic columns, the industry gold standard, have a limited binding capacity, are costly, and require familiarity with column maintenance, we are attempting, by our efforts, to help to produce a more efficient, simple, and economical purification platform.